Text Production for Novice Translators - Nurdin Bramono (Pioneer: Journal of Language and Literature, 2023)
Translator is a writer. This is an essential understanding for “novice” translators, especially students in higher education that learn translation studies. Some cases (see Annisa, (2020), Nurlaila(2021), Aprianti(2021) show that students in the language department faced difficulty to conduct translation tasks. Therefore, students or novice translators have to conduct a writing practice that may enhance their translation skills. As translation is involved in a writing activity, students (novice translators) have to understand that text production ability is essential. In this case, the ability to write especially in the target language is necessary to ease them in constructing the meaning or idea of the source text in the target language. Their brain will think aloud to investigate what to say (the idea of source text), perform text structuring (finding a proper word to realize the idea of source text language), expression (construct the words regarding on target language linguistic aspect) and revision (to check the result of translation, figuring out the wrong thing that led to reducing the meaning of source text). Thus, it is hoped that the result of the translation task will be accurate, acceptable and readable.